The noncanonical Gag domains p8 and n are critical for assembly and release of mouse mammary tumor virus - Zábranský, Ales; Hoboth, Peter; Hadravová, Romana; Stokrová, Jitka; Sakalian, Michael; Pichová, Iva (Journal of virology, 2010)
The mouse mammary tumor virus (MMTV) Gag contains the unique domains pp21, p3, p8, and n. We investigated the contribution of these domains to particle assembly and found that the region spanning the p8 and n domains is critical for shape determination and assembly. Deletion of pp21 and p3 reduced the number of released particles, but deletion of the n domain resulted in frequent formation of aberrant particles, while deletion of p8 severely impaired assembly. Further investigation of p8 revealed that both the basic and the proline-rich motifs within p8 contribute to MMTV assembly.
Keywords: Gene Products, gag; Mammary Tumor Virus, Mouse; myši; zvířata; virus myšího tumoru prsní žlázy; Protein Structure, Tertiary; Mice; Animals; genové produkty gag; sestavení viru; Virus Assembly; virové plášťové proteiny; terciární struktura proteinů; Capsid Proteins